Isotopic composition and pollen spectra of precipitation and ice at the edge part of Korumdu Glacier (North Chu ridge, Altai Mountains) - T. S. Papina; N. S. Malygina; T. A. Blyakharchuk; G. I. Nenasheva; N. A. Ryabchinskaya; A. N. Eyrikh (Лëд и снег)
The article presents results of study of the isotope composition and pollen spectra of atmospheric precipitation and ice taken from marginal parts of Korumdu Glacier (North-Chu Ridge, the Altai Mountains). The study was aimed at identification of sources and ways of precipitation into the nival-glacial region of Altai. Investigation of the isotope composition of ice taken from the tongue of the Korumdu Glacier and summer precipitation in its basin has shown that here the isotope concentrations are much smaller than similar ones of the cold Belukha Glacier. The last one is located near the Korumdu Glacier. This difference can be explained by the fact that main source of moisture forming layers of relatively warm Korumdu Glacier is precipitation of the cold season while accumulation on the cold Belukha Glacier proceeds during the whole year mainly due to the most heavy precipitation of warm (from March to November) season. Analysis of the isotope composition and the air mass trajectories on the day of July 16, 2013 allowed conclusion that the air masses started their way in the Baltic Sea region and moved mainly along middle latitudes. On this way they underwent insignificant isotope fractionation. Synoptic analysis had shown that the main reason of precipitation on the area under investigation was a front of occlusion over the Altai. In addition, results of palynological analysis of precipitation allow identification sources of pollen in this region. With high probability we can assume that on that day the main sources of pollen in Altai precipitation are as follows: the Naryan-Mar area for Scots pine (Pinus sylvestris) pollen, tundra zones of the East European Plain for alder (Alnaster sp.) pollen and the steppe regions of Kazakhstan, and the West Altai for pollen grains – the dominant component of the pollen spectrum.